Utilização de teste sorológico ELISA para a detecção de bovinos naturalmente infectados por Taenia saginata - Paulan, Silvana de Cássia [UNESP]; Gonzáles, Rutilia Marisela Hernándes; Peralta, Laura Adalid; Vicentini-Oliveira, Josy Campanhã [UNESP]; Biondi, Germano Francisco [UNESP]; Conde, Edda Sciuto; Parkhouse, Robert Michael Evans; Nunes, Caris Maroni [UNESP] (FapUNIFESP (SciELO), 2013)
Bovine cysticercosis, a cosmopolitan disease caused by Taenia saginata, leads to economic losses due to carcass devaluation at slaughter. Sanitary inspection at slaughterhouses, the routine diagnostic method in Brazil, lacks the necessary sensitivity to detect the mildly infected cattle that are typically encoutered in Brazil. In this study we have tested cattle sera from animals diagnosed as positive and negative by veterianry inspection for (1) anti-parasite antibodies using metacestodes antigens (T. solium vesicular fluid and T. saginata secretions) and (2) the HP10 secreted antigen of viable metacestodes. The cut-off values were calculated by ROC curve for intense and mild infections conditions, and by the classical method (X + 2DP for negative samples). The sensitivity and specificity of these diagnostic tests were different depending on the assumed cut-off value and, importantly, whether the infection was mild or intense. In spite of these observations, however, such ELISA assays for serum antibodies and parasite antigens constitute an important tool for epidemiological porposes, and in establishing priorities for the control of bovine cysticercosis.
Usefulness of serological ELISA assay for Taenia saginata to detect naturally infected bovines
Keywords: ELISA; Excretion-secretion; HP10 antigen assay; Sanitary inspection; Vesicular fluid